Scintigraphic Small Intestinal Transit Time and Defaecography in Patients with J-Pouch - Mie Dilling Kjaer; Jane Angel Simonsen; Svend Hvidsten; Jens Kjeldsen; Oke Gerke; Niels Qvist (Diagnostics, 2015)
Objective methods for examination of pouch function are warranted for a better understanding of the functional result and treatment of dysfunction. The objective of this study was to evaluate the results of scintigraphic intestinal transit time and defaecography compared to the results of pouch function, mucosal condition and a questionnaire on quality of life (QoL). This cross-sectional study included 21 patients. Scintigraphic transit time and defaecography was determined with the use of Tc-99m. Pouch function was assessed by number of bowel movements, pouch volume, and continence. Pouch mucosal condition was evaluated by endoscopy and histology. Median transit time was 189 min (105–365). Median ejection fraction at defaecography (EF) was 49% (3–77) and 62% (17–98) after first and second defecation. Median pouch volume was 223 mL (100–360). A median daily stool frequency of nine (4–25) was reported and three (14%) patients suffered from daytime incontinence. No patients had symptomatic or endoscopic pouchitis; however, the histology showed unspecific inflammation in 19 (90%) patients. There was no correlation between transit time, evacuation fraction (EF) and pouch function in univariate analysis. However, we found a high body mass index (BMI) and a low bowel movement frequency to be associated with a longer transit time by multivariate analysis. Scintigraphic determination of transit time and defaecography are feasible methods in patients with ileal pouch anal anastomosis, but the clinical relevance is yet doubtful.